Insights into the mitochondrial genome structure and phylogenetic placement of Theileria velifera in comparison to other apicomplexan parasites - Xing Yang; Shaobo Tang; Chaobo Du; Yuqing Chen; Zhi Luo; Miao Li; Shuang Liu; Mingna Duan; Dandan Jiang; Yujuan Shen; Quanfu Zhang; Chunhong Du (Scientific Reports)
Abstract In this study, we sequenced the complete mitochondrial genome of Theileria velifera and compared it with other Apicomplexan parasites. The mitochondrial genome of T. velifera is a linear monomer molecule spanning 6,125 bp, and it encodes 3 protein-coding genes (PCGs): cox1, cob, and cox3. Besides, it contains 5 large subunit (LSU) rRNA gene fragments and terminal inverted repeats (TIR) at both ends. Moreover, the mitochondrial genomes of most Apicomplexan parasites in this study are typically around 6,000 bp in length and are linear in structure, featuring three PCGs. The start codons observed in Thaleria spp. and Babesia spp. parasites predominantly include ATN, GTN, and TTN, while the end codons are mainly TAA, TAG, and TGA. Phylogenetic analysis showed that T. velifera was closely related to T. annulata, T. parva, T. taurotragi and T. lestoquardi. The complete mitochondrial genome sequence of T. velifera was examined and compared to other Apicomplexan parasites in this study, offering fresh perspectives on the evolution and phylogenetic connections among these parasites.